A Comparative Analysis of Western Nations’ Actions in Russia-Ukraine and Israel-Palestine Conflicts - Maulana, Muhammad Alfian (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2024)
This study explores and contrasts the responses of Western nations, specifically the United States (US), the United Kingdom (UK), and the European Union (EU), to two pivotal conflicts: the 2022 Russia-Ukraine conflict and the 2023 Israel-Palestine conflict. Adopting a multidisciplinary approach, the analysis delves into the political, historical, and humanitarian dimensions of these responses, aiming to unravel the intricate factors that shape Western foreign policy. Through a qualitative content analysis of diplomatic statements, and policy actions, the research discerns the motivations guiding the approaches of these key Western players to these conflicts. By using a comparative in foreign policy framework, a pivotal finding emerges, emphasizing that diverse in responses are primarily driven by interstate perspectives, thereby revealing nuanced positions influenced by varying regional alliances within the US, the UK, and the EU.